DOKUMEN ELEKTRONIK SEBAGAI ALAT BUKTI DALAM PERSPEKTIF PEMBARUAN HUKUM ACARA PERDATA INDONESIA - Muhammad Iqbal Tarigan; Runtung Runtung; Budiman Ginting; Dedi Harianto (USU LAW JOURNAL, 2016)
Electronic document is considered as evidence in the court’s verdict and in the Verdict of the Denpasar Higher Court No. 150PD/2011.Dps which recognizes email as legal evidence, whereas email is part of electronic document. However, the photograph which is a part of the document is not considered as evidence in the verdict. This is in line with the verdict of the Bondowoso Religious Court No 1537/Pdt.G/2011/PA.Bdw which states that sound record cannot be used as evidence although it is a part of the electronic document. Therefore, it is necessary to analyze the regulations concerning the use of electronic document as evidence in the Indonesian law of civil procedure and the criteria which can make electronic document as evidence in the law of civil procedure according to Law No. 11/2008 on Electronic Information and Transaction and on the Position of Electronic Document as Evidence in the innovation of the Indonesian law of civil procedure. Keywords: Evidence, Electronic Document, Innovation in Law